Confession and Confessors in the Templars’ Testimonies, 1307–1311: Notes on the Brothers’ Defence Strategy - Satora, Magdalena (The journal of ecclesiastical history, 2023)
This paper focuses on one of the elements employed in their defence by individual Knights Templar during the trials preceding the dissolution of the order: making reference to a previous confession made long before the start of the trials, in the course of which a brother divulged the sin of heresy. Questions are raised about the reliability of fragments of testimonies pertaining to this, the potential benefits that the Templars could have gained and the risks involved. An attempt is also made to indicate the source of this defence strategy, as well as the way in which it was disseminated among brothers interrogated at various times and in various places.